Model-based sizing of a CO2 heat pump for residential use. (October 2022) - Li, Yantong; Nord, Natasa; Halvorsen, Henrik; Håvard Rekstad, Inge
Highlights: A model-based sizing method for the CO2 heat pump is developed. An experimentally-validated quasi-dynamic CO2 heat pump model is developed. Effects of inlet water temperature in gas cooler and expansion valve opening on the performance are analysed. The optimal gas cooler surface area enlargement ratio can be identified by the developed sizing method in different compressor and expansion valve features. Abstract: CO2 heat pumps have advantages of reducing ozone layer damage and offering high-temperature hot water in comparison with traditional heat pumps. However, sizing of CO2 heat pump components that guarantees reliable performance is still challenging. Therefore, this study proposed a model-based sizing method to remedy this research gap. The quasi-dynamic model of the CO2 heat pump was developed by integrating dynamic and steady-state models. Model validation results demonstrated that average relative error for the outlet fluid temperature of evaporator and gas cooler were 7.8 % and 1.4 %, respectively. This indicated that the developed quasi-dynamic model was reliable. Modelling results indicated that coefficient of performance (COP) for the heat pump was 3.99 when the inlet water temperature in gas cooler and expansion valve opening were 24 °C and 28 %, respectively. The proposed model-based sizing method could effectively determine the optimal gas cooler area enlargement ratio in different compressor and expansion valve features. The results showed that higher priority to the operation and higer COP value, would favour larger gas cooler area, while higher priority on the investment cost would prefer lower gas cooler area. This study is useful to properly design and operate the CO2 heat pump.